Pengaruh Kombinasi Pupuk NPK Phonska dan Pupuk Tunggal (N, P, K) Terhadap Pertumbuhan dan Produksi Tanaman Padi Oryza Sativa. L - Syaiful Hidayat; Irba Djaja; Nicolas Mala (AGRICOLA, 2019)
This study aims to determine the growth and production of Oryza Sativa.L rice plants. using a combination of NPK and single Phonska fertilizer. The research method was Random Design Group (RBD) using experiments seven times with three replications. The results showed that the treatment of 35 hours of NPK N2 in plants averaged 80.26 cm. Plant height at 45 hours of NPK N2 treatment an average of 80.26 cm at age 60 hours in combination treatment of NPK N1 and NPK N2 was relatively the same at around 91.94 cm. At age 35 the number of first tillers in NPK N1 treatment averaged 17-19 tillers while at age 45 the average number of plants was 16.45 in NPK N2 treatment while at age 60 the first NPK N1 treatment to provide maximum number of tillers with an average 18.67 tillers and at the age of 90 the first treatment of NPK N2 was the number of tillers with an average productive of 12.82 tillers. Treatment of N2 NPK grains the average number of tillers 37.10 in the treatment of the number of N1 items NPK content with an average content of 86.40 panicles and in the treatment of NPK K2 gave a weight of 1000 seeds with an average of 29.67 gr in the treatment of dry grain gave P1 NPK harvest with an average of 673 tons / ha.